2008
DOI: 10.1109/tmag.2008.2001677
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of a One-Dimensional NÉel-Type Magnetic Domain Wall Resistance on Transverse External Magnetic Field in Presence of Rashba Spin-Orbit Coupling

Abstract: Domain walls in ferromagnetic metals are known to be a source of resistance. We have studied the resistance resulting from a onedimensional Néel-type magnetic domain wall in presence of Rashba spin-orbit coupling and external magnetic field. The analysis has been based on Boltzmann transport equation, within the relaxation time approximation. Through this formalism, we have shown that the spin-flip scattering and the resulting resistance originating from the Rashba spin-orbit coupling can be suppressed by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Therefore, increasing the photon wavelength which decreases the effect of the Zeeman interaction leads to DWR reduction. The similar DWR reduction by decreasing the external magnetic field [8] and increasing photon wavelength is reported in our previous studies [15] for 180°D Ws. To compare non-180°DWs with 180°DW, the resistance of 30°, 60°, and 180°DWs in the presence of xlinearly polarized photons is also shown in Figure 4.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Therefore, increasing the photon wavelength which decreases the effect of the Zeeman interaction leads to DWR reduction. The similar DWR reduction by decreasing the external magnetic field [8] and increasing photon wavelength is reported in our previous studies [15] for 180°D Ws. To compare non-180°DWs with 180°DW, the resistance of 30°, 60°, and 180°DWs in the presence of xlinearly polarized photons is also shown in Figure 4.…”
Section: Resultssupporting
confidence: 89%
“…From both scientific and technological points of view, understanding the resistance caused by DWs and determining the effect of different scattering sources on the DW resistance (DWR) are essential. For that reason, many research efforts have been made to understand the role of DW in resistivity [4][5][6][7][8][9][10][11][12][13][14][15]. Experiments on iron whiskers demonstrate that DWs are a source of electrical resistance [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of the Rashba interaction on the MR of a smooth domain wall in ferromagnetic materials has been studied, too. It has been shown that the spin-flip scattering and consequently the resistivity due to the domain wall increases monotonically with the Rashba interaction strength [20,21]. Similarly, the Dresselhaus spin-orbit interaction can affect the domain wall MR in the semiconducting magnetic structures.…”
mentioning
confidence: 99%